PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PERSONEL POLRI UNIT BINMAS DAN RESKRIM POLSEK CIKARANG BARAT - Hery Wihasnanto; Devi Harum Sari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose to analyze the influence of competency and work discipline on the performance of National Police personnel in the Binmas & Criminal Investigation Unit of West Cikarang Police. This research is included in the category of causal associative research using a quantitative approach. The sampling technique used a saturated sample. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the competency and work discipline on performance of National Police personnel in the Binmas & Criminal Investigation Unit of West Cikarang Police.